Patient Education for Patellofemoral Pain: A Systematic Review - Silva, Danilo De Oliveira [UNESP] (2020)
OBJECTIVE: To evaluate the effect of education interventions compared with any type of comparator on managing patellofemoral pain (PFP). DESIGN: Intervention systematic review. PROSPERO identifier: CRD42018088671. LITERATURE SEARCH: MEDLINE, Embase, CINAHL, and Web of Science were searched for studies evaluating the effect of education on clinical and functional outcomes in people with PFP. STUDY SELECTION CRITERIA: Two reviewers independently assessed studies for inclusion and quality. We included randomized controlled trials on PFP where at least 1 group received an education intervention (in isolation or in combination with other interventions). DATA SYNTHESIS: Available data were synthesized via meta-analysis where possible; data that were not appropriate for pooling were synthesized qualitatively. Interpretation was guided by the Grading of Recommendations Assessment, Development and Evaluation approach. RESULTS: Nine trials were identified. Low credibility evidence indicated that health education material alone was inferior to exercise therapy for pain and function outcomes. Lowand very low-credibility evidence indicated that health professional-delivered education alone produced outcomes similar to those of exercise therapy combined with health professional-delivered education for pain and function, respectively. CONCLUSION: Health professional-delivered education may produce similar outcomes in pain and function compared to exercise therapy plus health professional-delivered education in people with PFP.